Shape memory alloy torsional actuators: a review of applications, experimental investigations, modeling, and design. (22nd October 2020) - Stroud, H; Hartl, D
Abstract: Simplicity, volume, dimensions, and often mass are important factors in mechanical systems; engineers are looking to smart materials, in particular shape memory alloys (SMAs), to provide actuation and dampening capabilities in highly compact packages. SMAs have long been studied for their potential to impact a number of disciplines, especially the aerospace, biomedical, and automotive industries. However, while axial SMA actuation (e.g. in the form of wires) is highly common and has been extensively reviewed, no comprehensive compilation of studies in SMA torsional actuation is provided in existing literature. It is one of the most compact possible approaches to supplying rotational motion under load. This paper reviews the torsional applications of SMAs and their properties in that regard. First, a brief overview of SMA behavior is given. A review of applications past and present incorporating torsional SMAs is reported, and a summary of experimental data provided in prior literature, essential for understanding real-world capabilities of SMA torsional actuators, is presented. A modeling approach is outlined, and theoretical torque tube performance is demonstrated as compared to prior experimental data. The work concludes with a discussion of future developments required to enable commercial applications of SMA torque tubes.